THE EFFECT OF ACCOUNTING CONTROLS AND REPORTING SYSTEMS ON PERFORMANCE ACCOUNTABILITY THROUGH LEADERSHIP AS AN INTERVENING VARIABLE IN REGENCY REGIONAL FINANCIAL AND ASSET AGENCIES EAST LUWU - Sriyani Amri; Antong; Muammar Khaddapi; Syafruddin, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research aims to examine the relationship and influence of Accounting Control and Reporting Systems on Performance Accountability through Leadership as an Intervening variable in the East Luwu Regional Financial and Asset Agency. The research methodology was carried out using quantitative methods by conducting a Patrial Squere Test, using research samples with primary data sources, namely Kuisinoer. Research Location at the East Luwu Regency Regional Financial and Asset Agency. The results found from the research show that accounting control has no effect on performance accountability. The Reporting System has an influence on Performance Accountability. Accounting controls have no effect on leadership. The Reporting System influences leadership. Leadership influences performance accountability. Accounting controls have no effect on performance accountability through leadership. The reporting system influences performance accountability through leadership.